Economic burden of cardiovascular diseases among elderly patients in Iran: a case from a developing country - Mohammad Tasavon Gholamhoseini; Sepideh Arjomand Kermani; Vahid Yazdi-Feyzabadi; Reza Goudarzi (BMC, 2024)
Abstract Background Cardiovascular diseases (CVDs) are the leading cause of mortality and morbidity worldwide, particularly among the aging population. This study aims to evaluate the economic burden of CVDs among Iranians aged 60 years and older. Methods A cost-of-illness study was conducted using a prevalence-based approach from a societal perspective. Cost analysis employed the bottom-up micro-costing method to assess direct medical and non-medical costs, while indirect costs were calculated using the human capital approach. Data were sourced from medical records of individuals aged 60 and older with CVDs registered in the hospital information systems of public and private hospitals in southeastern Iran. Additionally, structured face-to-face interviews were conducted with 160 caregivers or relatives serving as companions of elderly patients, using a structured questionnaire to gather data on healthcare utilization. Sensitivity analyses were performed, along with projections of the future economic burden of CVDs. Results The annual total cost of CVDs among people aged 60 years and above in Iran was estimated at US$ 1,885,091,171.7 (about 1.88 billion), equivalent to 1.27% of the Iran's GDP in 2021. Direct medical costs accounted for 90.62% of the total, with 54.72% attributed to ambulatory care. The average cost of CVDs per patient was US$ 446.2. The results of two-way sensitivity analysis provided an estimated cost range between US$ 1.2 billion and US$ 2.7 billion. By 2030, the total cost of CVDs is projected to reach US$ 21 billion. Conclusions The elderly population with CVDs imposes a growing economic burden on Iran's healthcare system and society. This underscores the urgent need for effective and cost-effective interventions to prevent and manage CVDs in Iran.